2003
DOI: 10.1159/000068743
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Is Associated with Severe Acute Ischemic Stroke

Abstract: Atrial fibrillation (AF) is a common risk factor for disabling ischemic stroke in the elderly, but it is not clear that its severity is generally worse than that of ischemic stroke due to other etiologies. We reviewed the clinical presentations of patients with acute ischemic stroke admitted between 1990 and 2001. The etiologies of these strokes were also classified using well-established criteria. Of 1,061 patients with acute ischemic stroke, 216 (20.3%) had AF. The frequency of bedridden state was 41.2% in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
3
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(139 citation statements)
references
References 18 publications
5
110
3
16
Order By: Relevance
“…All these aforementioned associations have been identified in prior work. [12][13][14][15] Our study has some limitations. This was a single center study, in which patients were not randomized, and we did not collect data on the exact timing of bilirubin levels or stroke severity assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these aforementioned associations have been identified in prior work. [12][13][14][15] Our study has some limitations. This was a single center study, in which patients were not randomized, and we did not collect data on the exact timing of bilirubin levels or stroke severity assessment.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the role of possible confounding factors, other potential determinants of incident stroke severity were also analyzed based on prior reports in the literature: age, sex, history of atrial fibrillation, history of hypertension, hyperlipidemia, diabetes, smoking status, admission glucose, premorbid antithrombotic use, premorbid statin use, and premorbid functional status. [12][13][14][15][16][17] Potential baseline covariate predictors of functional status at hospital discharge included all the aforementioned potential determinants of stroke severity and admission NIHSS score. 12 The pool of potential covariates (listed above) were then selected using backward elimination at P =.2.…”
Section: Methodsmentioning
confidence: 99%
“…3,26 The oral anticoagulant therapy currently available in the public healthcare system in Brazil is warfarin. It is recommended that the care for patients using oral anticoagulant therapy with warfarin should be provided in anticoagulation clinics, 14 because these have been shown to be more effective in controlling these patients' coagulation in terms of efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most commonly sustained arrhythmia globally and results in significantly increased morbidity and mortality, including a fivefold risk of stroke [1]. Recent studies have shown that stress, anxiety, sadness, and anger each increase the likelihood of AF development, whereas happiness is protective [2].…”
Section: Introductionmentioning
confidence: 99%